Business Cycle and Stability of China’s Financial and Monetary System - Wang, William Hongson; García, Antonio Vegas (REVISTA PROCESOS DE MERCADO, 2017)
The importance of China’s economy and the instability of China’s fi-nancial system are in the spotlight recently. This paper uses Austrian Business Cycle Theory to gauge the potential risks of China’s economy. The approach of this paper is a sector analysis, focusing on China’s monetary and financial system, shipping industry, and real estate industry, especially the state-owned enterprises in those sectors. We conclude that China’s central banking system is hurting China’s economy and we also propose reforms to overhaul the system, according to the perspective of praxeology and Austrian School Econom-ics. Keywords: Austrian Business Cycle Theory, China’s banking system, China’s economy. JEL Classification: B53, D8, E310, E32, E52, H12, N15, N27, N45, N65, O53, P11, R3, R4, Y10. Resumen: La importancia de la economía china junto con la reciente inestabili-dad del sistema financiero de China, preocupan al resto del mundo. Este artí-culo usa la Teoría Austriaca del Ciclo Económico para identificar los riesgos potenciales de la economía de China. En este artículo realizaremos un análisis sectorial, enfocado en el sistema monetario y financiero de China, el sector de la construcción, la industria marítima y, en especial, las empresas estatales de dichos sectores. Concluimos que el actual sistema de banca central en China está dañando a su economía y proponemos soluciones desde la perspectiva de la praxeología y la Escuela Austriaca de Economía. Palabras clave: Teoría austriaca del ciclo económico, sistema bancario chino, economía china.